Hubungan Karakteristik Ibu, Riwayat Pemberian Asi Eksklusif dan Sanitasi Lingkungan terhadap Kejadian Stunting pada Bayi Umur 2-5 Tahun di Puskesmas Siatas Barita - Janner Pelanjani Simamora; Hutabarat, Naomi Isabella (EMBRIO, 2021)
Toddler period is a crucial period in the process of human growth and development, growth and development in toddlers at this time is very influential for the success of growth and development of toddlers at the next stage. Lately, the problem of malnutrition that has received the most serious attention is the problem of stunting. The problem in this study is the high prevalence of stunting for infants aged 2-5 years at the Siatas Barita Health Center as much as 201 out of 1035 toddlers. The purpose of this research was to analyze the relationship between maternal characteristics (knowledge, education, occupation, income, number of families), history of exclusive breastfeeding and environmental sanitation with the prevalence of stunted children in Siatas Barita Public Health Center. This study uses an observational analytic design with a cross-sectional case approach. The targets in this study were 193 mothers who had babies aged 2-5 years. Sampling uses the convenience technique. Data obtained by questionnaire, and analyzed using multiple regression in = 5%. The results showed the variables of knowledge (p value 0.02 <0.05), education (p value 0.035 <0.05), history of exclusive breastfeeding (p value 0.018 <0.05) and environmental sanitation (p value 0.033 <0 0.05) was related to the incidence of stunting while occupation (p value 0.205> 0.05), income (p value 0.779> 0.05) and the number of families (p value 0.663> 0.05) were not related to the incidence of stunting. The knowledge variable has a significant effect on the prevalence of short children at the Siatas Barita Health Center.